Efficacy and safety of long-term treatment with statins for coronary heart disease: A Bayesian network meta-analysis. (November 2016) - Lu, Yongbin; Cheng, Zhiyuan; Zhao, Yaxue; Chang, Xiaoyu; Chan, Cynthia; Bai, Yana; Cheng, Ning
Abstract: Background and aims: Our study aims to evaluate the efficacy and safety of long-term treatment of statins for coronary heart disease (CHD). Methods: Efficacy outcomes included changes in blood lipids, risk of CHD mortality and all-cause mortality. Safety outcomes were evaluated by the risk of adverse events (AE). Bayesian network meta-analysis was used to compare the direct and indirect effects between different statins. Results: The systematic review showed that levels of blood lipids decreased during statin treatment. High dose of atorvastatin was the most obvious treatment for the reduction of blood lipids. Network meta-analysis showed that statins were significantly more effective than the control in reducing the risk of CHD mortality (Odds Ratio (OR) 0.69, 95% CI 0.61–0.77) and all-cause mortality (OR 0.84, 95% CI 0.80–0.87). In terms of reducing the risk of CHD morality, fluvastatin (77.3%), atorvastatin (72.3%) and lovastatin (68.4%) had higher cumulative probability than other statins, which were more effective treatments for the reduction of CHD morality. In terms of reducing all-cause mortality, atorvastatin (78.6%), fluvastatin (77.1%) and pitavastatin (74.1%) had higher cumulative probability than other statins, which were more effective treatment for reducing the all-cause mortality. Compared with placebo, statins increased the incidence risk of muscle disease (OR 1.05, 95% CI 1.00–1.10) and kidney disease (OR 1.11, 95% CI 1.05–1.72). Conclusions: Statins significantly reduced levels of blood lipids, with a high dose of atorvastatin being the most effective in blood-lipid level modification. Statins reduced the risk of CHD mortality and all-cause mortality, with atorvastatin and fluvastatin being the most effective in reducing the risk of CHD mortality and all-cause mortality. Statins increased the risk of muscle disease and kidney damage. Highlights: Used a Bayesian network meta-analysis to study CHD with using different statins. Studied the efficacy and safety for treatment CHD with using different statins. Only considered prospective cohort study, which has reliable data, less recall bias, better explain causal relationships. Outcome included not only clinical indicators, but also ultimate outcomes, which better explained which statin is the best choice.